A novel bi‐directional high‐gain DC‐DC converter with optimum number of components. (2nd September 2022) - Krishna, Bekkam; Karthikeyan, V.
Abstract: Most emerging applications of battery energy storage systems, fuel cells, and unified power supply (UPS) applications require essential bi‐directional power capability with a high conversion ratio. It supports the integration of the high‐voltage DC‐bus with an energy storage unit or fuel cell. In order to meet this requirement, this paper proposes a novel nonisolated high‐gain DC‐DC converter with bi‐directional power flow capability. This converter is configured with a hybrid structure with a combination of the switched capacitor (SC) and switched inductor (SI) techniques. Moreover, this converter can attain extreme voltage gain with less number of semiconductors and passive components. As a result, the converter cost gets reduced and achieves a wide range of voltage gain at a lesser duty ratio. Furthermore, steady‐state analysis and performance of the proposed topology and its characteristics were presented in this paper. Additionally, a detailed comparative analysis was presented with the most recent literature. Finally, a 500‐W experimental prototype has been fabricated to authorize the performance, feasibility, and analytical waveforms with experimental results. Abstract : This paper proposes a novel nonisolated high‐gain dc‐dc converter with bi‐directional power flow capability. It supports the integration of the high‐voltage DC‐bus with an energy storage unit or fuel cell. This converter can attain extreme voltage gain with less number of semiconductors and passive components. As a result, the converter cost gets reduced and achieves a wide range of voltage gain at a lesser duty ratio.